Pengembangan Fungsi Clay Sebagai Pengharum Mobil - Yovita Gunawan; Pramesti Saniscara (Jurnal Vicidi, 2018)
“Craftivity” is a business engaged in the creative industry that make orproduce toys made from clay shaped figure and has a function as car fragrances. Currently no one has sold clay based figures that have car fragrances function. So the purpose of this study is to find out the target market demand. Using Quantitative and qualitative research methods. What we get is that most of the consumers agree on custom product figures that suit their own desires to add car fragrances functionality. This can be a business opportunity for craftivity.